Unlawful occupation of state land in Malaysia and its implications - Mohamed Osman, Mariana; Bachok, Syahriah; Abdullah, Muhammad Faris; Zahari, Rustam Khairi; wahab, hanisah (American Scientific Publishers, 2017)
This paper discusses the unlawful occupation of State land in Malaysia and its implications. This paper identifies the types and the nature of unlawful occupation of State land or Government land. The study is to provide an overview and descriptive analysis of the situation and the efforts done by the local authorities in addressing the issues. It then discusses several cases of unlawful occupation of State land by drawing examples from cases involving illegal factories and illegal farming from different states in Malaysia. Most of the illegal operators tend to occupy government land without permission of the owner i.e. the government. The study identified the main adverse effects of illegal encroachment on state land are in term of the loss of state revenue and the adverse environmental effect to the surrounding area. Cases of the illegal occupation of state land like in Cameron Highland in Pahang and Tapah in Perak have led to landslide and flood that effect the surrounding residential areas and the town of Cameron Highland1, 2. The state governments in Selangor, Perak and Pahang have applied various enforcement methods in addressing the problems. However, the issues remain unsolved as most of these activities were done in the remote location of rural and forest areas. It is hoped that the discussion will provide positive input in providing some guidelines and solution to the issue of illegal encroachment on state land in Malaysia.